Communicate like a leader - Newbold, Curtis (O'Reilly Media, Inc., 2024)
Communication is a multifaceted skill that facilitates the flow of information and collaboration in the workplace. These shortcuts provide concise, actionable guidance on how to improve your skills across different communication types and channels, helping you become a more efficient, persuasive, and effective communicator.
Keywords: Communication in management; Leadership; Communication en gestion